Unveiling enhanced oxidation resistance and mechanical integrity of multicomponent ultra‐high temperature carbides. Issue 4 (23rd December 2021) - Nisar, Ambreen; Dolmetsch, Tyler; Paul, Tanaji; Sakthivel, Tamil Selvan; Zhang, Cheng; Boesl, Benjamin; Seal, Sudipta; Agarwal, Arvind
Abstract: The development of a new class of multicomponent ultra‐high temperature ceramics (MC‐UHTCs), often referred to as high‐entropy UHTCs, has gained increased interest due to the possibility of improved thermomechanical and oxidation properties. In this study, a systematic approach by gradual addition in the UHTC components ranging from a binary to a dense quaternary (Ta, Nb, Hf, Ti)C is synthesized using spark plasma sintering (SPS). The solid solutioning was the critical factor in homogenizing the composition in the multicomponent system. The segregation of NbC and HfC was seen in binary and ternary UHTC systems, while a single‐phase homogeneity was observed in the quaternary UHTC improving its hardness up to 34.8 GPa. The presence of closely spaced slip lines in the MC‐UHTCs enhances resistance to indentation damage up to 72% at an applied load of 200 N. The formation of complex mixed oxide phase of Hf6 Ta2 O17 ensued in the lower to negligible oxidation even up to 3 min of plasma exposure with temperature exceeding 2800°C. In sum, though the entropy remains medium (0.96 R ) for the selected system, the quaternary UHTC system undoubtedly has significantly better thermomechanical performance when compared to established baseline UHTCs. This raises the debate on the justification for calling a multicomponent system a "high entropy" to be seen in a new light. The developed MC‐UHTCs elicits the paradigm of this new class of UHTCs expanding their potential in thermal protection systems for hypersonic applications.